The Clinical Differences of Patients With Traumatic Brain Injury in Plateau and Plain Areas - Yang, Yongxiang; Peng, Yuping; He, Siyi; Wu, Jianping; Xie, Qingyun; Ma, Yuan (Frontiers in Neurology, 2022)
Objective Traumatic brain injury (TBI) is a leading cause of death and disability, which tends to have worse clinical recovery if it occurs in plateau areas than in plain areas. In order to explore the underlying cause of this outcome preliminarily, this retrospective study was conducted to compare the clinical differences of patients with TBI in plateau and plain areas. Methods Thirty-two TBI patients in plateau areas (altitude≥4000 m) and thirty-two TBI patients in plain areas (altitude≤1000 m) were recruited according to the inclusion and exclusion criteria from June 2020 to December 2021. The collected data and compared parameters including clinical features, head CT presentations and Marshall classifications, hematology profile, lipid profile, coagulation profile and multiorgan (cardiac, liver, renal) function within 24h of hospital admission, as well as the treatment method and final outcome. Results There were no obvious differences of demographic characteristics including gender, age, height and weight between patients with TBI in plateau and plain areas (all P＞0.05). Compared to patients with TBI at plain areas, time before hospital admission was longer, heartbeat was slower, systolic blood pressure (SBP) was lower and hospital stays was longer in patients with TBI at plateau areas (all P＜0.05). More importantly, elevated red blood cells (RBCs) counts and hemoglobin (HGB) level, enhanced coagulation function and higher rates of multiorgan (cardiac, liver, renal) injury was found in patients with TBI at plateau areas (all P＜0.05). Conclusion TBI patients in plateau areas presented with altered clinical characteristics, enhanced coagulation function and aggravated predisposition toward multiorgan (cardiac, liver, renal) injury, compared with TBI patients in plain areas. Future prospective studies are needed to further elucidate the influences of high altitude on the disease course of TBI.